Dialektika Filsafat Islam Sufistik Wujuddiyah Di Indonesia - Syaifan Nur (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2017)
The first Islamic philosophy that emerged in Indonesia was the Islamic philosophy that had been linked to Sufism, or Sufistic Islamic philosophy, namely Islamic philosophy in Sufism. This is called tasawwuf falsafi. This type is based on the dzauq and ‘irfân which is different from the rational system of rational reasoning. In Indonesia, the philosophical conversation in the earliest of the philosophy of Sufism appeared in the 16th century AD In this period, the philosophical style of Sufism was taught by such figures as Hamzah Fansuri and Shamsuddin al-Sumatrânî. The monistic idea Fansuri expanded and formed the central core of the teachings and writings of al- Sumatrânî. Both are the main characters of the interpretation of the concept of wahdah al- wujûd, which is philosophical-sufistic. The influences of Fansuri and al-Sumatrân teachings are not only found in Aceh, but also to the land of Java. The philosophical Sufism of wujûdiyyah or tasawuf falsafî was strongly opposed by many scholars of the time, especially from orthodox oriented syarî’ah. The most harsh and intolerant opponent and critic of this notion is Nur al-Din al-Raniri. Repudiation and al-Raniri’s opposition to Sufistic philosophy wujûdiyyah of Fansuri is based on some evidence that he considers it deviated from pure Islamic teachings.[Filsafat Islam yang muncul pertama kali di Indonesia adalah filsafat Islam yang telah berkait-kelindan dengan tasawuf, atau filsafat Islam sufistik, yakni filsafat Islam dalam baju tasawuf. Ini disebut tasawuf falsafî. Jenis ini didasarkan pada dzauq dan ilmu ‘Irfân yang berbeda dengan sistem penalaran rasional yang ketat. Di Indonesia, perbincangan filosofis dalam corak tasawuf falsafî yang paling dini muncul pada abad ke-16 M. Pada periode ini, corak filosofis dari tasawuf diajarkan oleh tokoh-tokoh seperti Hamzah Fansuri dan Syamsuddin al-Sumatrânî. Gagasan monistik Fansuri diperluas dan membentuk inti pokok ajaran-ajaran dan tulisan-tulisan al-Sumatrânî. Keduanya merupakan tokoh utama penafsiran konsep wahdah al-wujûd, yang bersifat sufistik-filosofis. Pengaruh ajaran Fansuri dan al-Sumatrânî tidak hanya ditemukan di Aceh, tetapi juga sampai ke tanah Jawa. Paham filsafat sufistik wujûdiyyah atau tasawuf falsafî ditentang keras oleh banyak ulama saat itu, terutama dari kalangan ortodoks yang berorientasi syarî‘ah. Penentang dan kritikus yang paling keras dan paling tidak toleran terhadap paham ini adalah Nuruddin al-Raniri. Sanggahan dan penentangan al-Raniri terhadap filsafat sufistik wujûdiyyah Fansuri didasarkan atas beberapa bukti yang dianggapnya telah menyimpang dari ajaran Islam yang murni.]